USABILITY DAN REDESIGN UI/UX WEBSITE SMA ANGKASA 1 JAKARTA DENGAN METODE USER CENTERED DESIGN DAN SYSTEM USABILITY SCALE - Muhammad Irfan Ajisoko (2024)
Angkasa 1 Jakarta High School is a school under the auspices of the Halim Perdanakusuma Indonesian Air Force Education Cooperation Agency (BKSP) which was founded in 1983. Angkasa 1 Jakarta High School has an official website address as a means of informing teachers, students and the general public. who want to know information about the school. Angkasa 1 High School has several features such as the school's vision and mission, brief history, superior programs, photo gallery, information and teachers. However, a website must be supported by a good, attractive interface and in accordance with user needs so that the website is easy for users to understand. After conducting a survey with website managers and questionnaires to website users, it was found that the website did not have a user friendly appearance, the website structure also did not have a good structure, this caused visitors to experience difficulty in selecting and searching for the information they wanted and there was a lack of extracurricular page features. which can contain extracurricular information and schedules provided by the school. This can be seen on the dashboard page where the content of articles, announcements and brief information about the school overlap, causing visitors to have difficulty selecting and reading the information listed. In the navigation section, which is a menu that functions to direct users to other pages, it has not been arranged. and placed in a good location, there are also navigation font sizes and colors that are contradictory, which can cause users to be confused when using the Navigation Bar. Apart from that, on the Angkasa 1 Jakarta High School website, there is an inappropriate size and layout of information on the page so that the dashboard display gives a monotonous impression. This research aims to analyze and provide an assessment of the user experience and redesign the user interface using a User Centered Design approach to focus on users of the SMA Angkasa 1 website. This research will produce a new interface in the form of a prototype that can be used as a suggestion for SMA Angkasa 1 and will be tested using the System Usability Scale (SUS).